Effect of eccentric exercise-induced fatigue on proprioception, motor control and performance of the upper limb in handball players - Hadjisavvas, S.; Efstathiou, M. A.; Themistocleous, I.-C.; Daskalaki, K.; Papamichael, E.; Michailidou, C.; Rentzias, P.; Pavlou, K.; Savva, C.; Stefanakis, M. (Sport Sciences for Health, 2025)
During the deceleration phase of handball throwing, the rotator cuff experiences significant tensile forces due to its eccentric action, which can potentially lead to injury. It is widely thought that fatigue, particularly during eccentric exercise, has a detrimental effect on proprioception. However, there are limited researches about the effect of eccentric fatigue on shoulder proprioception. As far we know, there has been no research conducted to examine the impact of eccentric exercise-induced fatigue on motor control and performance of upper extremities. The purpose of this study was to investigate the effect of eccentric exercise-induced fatigue on proprioception, motor control and performance of the upper limb in handball players. A total of thirty-three male professional handball players participated in the recruitment process. The shoulder proprioception was assessed using the joint repositioning sense (JRS) and the threshold to detection of passive movement (TTDPM). Motor control and performance were assessed using the Y balance upper quarter test (YBT-UQ) and the athletic shoulder test (ASH) respectively. All outcome measures were evaluated before and immediately following the eccentric fatigue intervention. Eccentric exercise-induced fatigue was generated by requiring participants to exert maximum resistance against the dynamometer's forced internal or external rotation while moving through a range of motion from 60° of external rotation to 60° of internal rotation. After the fatigue intervention, there were significant impairments in JRS (p < 0.05), TTDPM (p = 0.011), motor control (p < 0.05), and performance (p < 0.05) of the upper extremity. These findings provide significant information about the detrimental effect of fatigue in athletes. Strategies which aim to increase both fatigue resistance, proprioception, motor control and performance are necessary to reduce the likelihood of handball injuries.